Contributing to an European vision of democratic education by engaging multiple actors in shaping responsible research agendas - Gudowsky, Niklas; Sotoudeh, Mahshid; Bechtold, Ulrike; Peissl, Walter (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
Traditionally, expert-based forward looking has been applied to anticipate future challenges, solutions and strategic decisions, but limitations to this approach have become obvious – especially when considering long term perspectives – e.g. failing to include a comprehensive array of opinions. Aiming at producing sustainable strategies for responsible socio-technical change, research funding can benefit from combining forward looking and public participation to elicit socially robust knowledge from consulting with multi-actors, including citizens. In this paper, we give insights into the EU project CIMULACT – Citizen and Multi- Actor Consultation on Horizon 2020. In CIMULACT, more than 4500 citizens, stakeholders and experts from 30 European countries engaged online and offline to co-create research topics. These are supposed to serve as input for the next round of calls in Horizon 2020, national research agendas as well as the ninth framework programme in the making. We investigate key results of this transdisciplinary process focussing on the topic “democratic education” with regard to two levels: What issues concerning the topic were raised? Can we find a common European imaginary for “democratic education”? Our analysis shows that the results contribute to defining and describing challenges for the currently prevailing imaginary of democratic education in Europe.